2009
DOI: 10.1007/s00586-008-0880-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of kyphoplasty with use of a calcium phosphate cement and non-operative therapy in patients with traumatic non-osteoporotic vertebral fractures

Abstract: One of the current standard treatment options for younger patients with stable traumatic vertebral fractures is conservative treatment using braces. Kyphoplasty as a minimally invasive procedure has been shown to be effective in stabilizing vertebral body fractures, resulting in immediate pain relief and improved physical function. The purpose of this prospective study was to clarify whether patients with acute traumatic vertebral fractures benefit more from kyphoplasty or from conservative treatment with a br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Unlike BKP, in vertebroplasty bone cement is injected into the vertebra at high pressure and free: so cement-leakage rate is higher, especially if there are many fracture cracks, such as for traumatic VCFs [Schmelzer et al, 2009]. In his meta-analysis on 69 clinical studies, Hulme [Hulme et al, 2006] reported leakage rates in 41% of cases during vertebroplasty and in 9% of cases during BKP.…”
Section: Alternative Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike BKP, in vertebroplasty bone cement is injected into the vertebra at high pressure and free: so cement-leakage rate is higher, especially if there are many fracture cracks, such as for traumatic VCFs [Schmelzer et al, 2009]. In his meta-analysis on 69 clinical studies, Hulme [Hulme et al, 2006] reported leakage rates in 41% of cases during vertebroplasty and in 9% of cases during BKP.…”
Section: Alternative Proceduresmentioning
confidence: 99%
“…The most commonly described complication is an extravertebral leakage of bone cement [Groen et al, 2004], more likely in traumatic VCFs compared to pathologic VCFs due to more fracture cracks in traumatic fracture [Schmelzer-Schmied et al, 2009]. The systematic review of the literature by Hulme found rates of cement leakage in vertebroplasty of 41% (n = 2283 levels) and in kyphoplasty of 9% (n = 1486 levels) of treated vertebrae.…”
Section: Complicationsmentioning
confidence: 99%
“…The success of this material is based on immediate relief of pain and mechanical stabilization improving physical functions [3,8] as well as low cost [9]. However, clinical trial results have exposed a high complication rate in percutaneous vertebroplasty with PMMA range from 1 to 10 % [10,11], highlighting potential weaknesses such as thermal injury to surrounding tissues, potentially causing neurological damage, increasing fracture risk at adjacent levels due to the high inherent stiffness, and potential toxicity caused by the reactive material [2,4,9,12].…”
Section: Introductionmentioning
confidence: 97%
“…Both procedures are today proven and accepted as standard of care for pain caused by compression fractures of the spine, such as traumatic non-osteoporotic vertebral fractures and traumatic compressive vertebral collapses, especially in younger patients [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation